2018
DOI: 10.1128/aem.01031-18
|View full text |Cite
|
Sign up to set email alerts
|

Nitrosospira Cluster 8a Plays a Predominant Role in the Nitrification Process of a Subtropical Ultisol under Long-Term Inorganic and Organic Fertilization

Abstract: Long-term effects of inorganic and organic fertilization on nitrification activity (NA) and the abundances and community structures of ammonia-oxidizing bacteria (AOB) and ammonia-oxidizing archaea (AOA) were investigated in an acidic Ultisol. Seven treatments applied annually for 27 years comprised no fertilization (control), inorganic NPK fertilizer (N), inorganic NPK fertilizer plus lime (CaCO) (NL), inorganic NPK fertilizer plus peanut straw (NPS), inorganic NPK fertilizer plus rice straw (NRS), inorganic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 74 publications
(115 reference statements)
2
17
0
Order By: Relevance
“…However, this phenomenon seems to occur only in soils with low pH and substrate availability. In the soils with inorganic N additions or relatively high pH, AOB is still the main players [ 82 , 83 ], as reported by Lin et al [ 68 ], who observed a shift from AOA to AOB accompanied by an increase in pH of an acidic soil after 44 years of pig manure and inorganic N additions. Microorganisms carrying nirK and nirS denitrifying genes are also sensitive to pH change and, as mentioned earlier, to changes in C availability [ 84 ].…”
Section: Effects Of Organic Fertilizers On Nitrifying and Denitrifying Soil Microorganismsmentioning
confidence: 97%
See 1 more Smart Citation
“…However, this phenomenon seems to occur only in soils with low pH and substrate availability. In the soils with inorganic N additions or relatively high pH, AOB is still the main players [ 82 , 83 ], as reported by Lin et al [ 68 ], who observed a shift from AOA to AOB accompanied by an increase in pH of an acidic soil after 44 years of pig manure and inorganic N additions. Microorganisms carrying nirK and nirS denitrifying genes are also sensitive to pH change and, as mentioned earlier, to changes in C availability [ 84 ].…”
Section: Effects Of Organic Fertilizers On Nitrifying and Denitrifying Soil Microorganismsmentioning
confidence: 97%
“…Ammonia oxidizers are particularly sensitive to the supply of NH 4 + since they are lithoautotrophic microorganisms. Thus, animal manures typically increase the abundance and activity of ammonia oxidizers, leading to overall high nitrification rates [ 56 , 68 ]. While mineralization kinetics of organic N depends on environmental conditions and C:N ratios of the manure, nitrification of NH 4 + proceeds relatively quickly, especially under high temperature and oxygen availability.…”
Section: Effects Of Organic Fertilizers On Nitrifying and Denitrifying Soil Microorganismsmentioning
confidence: 99%
“…Dominant OTUs (relative abundance >1%) were taxonomically classi ed through constructing neighbor-joining phylogenetic trees in the MEGA7 software (Kumar et al 2016) using representative sequences of AOA or AOB amoA genes and taxonomically determined reference sequences. Reference sequences for AOA clusters were from Alves et al (2013) and Lin et al (2019), and for AOB clusters were from and . Diversity (Shannon) and richness (Chao1) of AOA and AOB were calculated by the QIIME.…”
Section: High-throughput Sequencing and Bioinformatic Analysesmentioning
confidence: 99%
“…Burkholderia and Mesorhizobium have been widely reported to have nitrogen xation capabilities (Fan et al, 2019;Soe et al, 2020), and their abundances were signi cantly higher in the rhizosphere soils with NT and RT than in those with MP. OTU2806 (Nitrosospira multiformis) and OTU3942 (Nitrosospira tenuis), which play a pivotal role in the nitri cation process (Lin et al, 2018), were enriched in the bulk soils with RT and rhizosphere soils with NT. OTU4404 (Bradyrhizobium japonicum) and OTU2109 (Rhizobium etli) are widely documented to facilitate nodulation and biological nitrogen xation of legumes (Kalita and Malek, 2020; Rivas et al, 2009; Roper et al, 2020), and they increased in the rhizosphere soils with NT and RT.…”
Section: Variations In Soil Bacterial Community Compositions Induced By Different Tillage Practicesmentioning
confidence: 99%